The Effect of Market Structure on Bank Performance in Central Java - Imanuel Madea Sakti (Faculty of Economics Universitas Negeri Yogyakarta in collaboration with the Institute for, 2020)
Abstract: The research on the Structure-Conduct-Performance (SCP) hypothesis in the banking industry has been done many times, including in Indonesia. However, it still focuses on commercial banks. This research aims to examine the relationship between market structure and bank performance by involving commercial banks and rural banks (Bank Perkreditan Rakyat/BPR) when they are in the same market in the regency/city level. It uses panel data from 565 banks in Central Java: 261 BPR and 304 Commercial Banks, divided into 34 regencies/cities during 2012-2016. Independent variables involve market concentration and market share which is also as moderating variable, and the dependent variable is bank performance. The hypotheses are examined by multiple linear regression with a random effect model. In general, the results support that the market structure has a significant positive effect on bank performance. Another result has found no collusive behavior among dominant banks. Keywords: Structure-Conduct-Performance, Commercial Bank, Rural Bank, Market Structure, Bank Performance Pengaruh Struktur Pasar terhadap Kinerja Bank di Jawa Tengah Abstrak: Penelitian mengenai hipotesis Structure-Conduct-Performance (SCP) pada industri perbankan telah banyak dilakukan, termasuk di Indonesia. Namun, penelitian tersebut hanya berfokus pada bank umum saja. Penelitian ini bertujuan untuk menguji hubungan antara struktur pasar dan kinerja bank dengan melibatkan bank umum dan Bank Perkreditan Rakyat (BPR) ketika berada di pasar yang sama di tingkat kabupaten/kota. Penelitian ini menggunakan data panel terdiri dari 565 bank di Jawa Tengah: 261 BPR dan 304 Bank umum, yang terbagi ke dalam 34 kabupaten/kota selama tahun 2012-2016. Variabel independen yaitu konsentrasi pasar dan pangsa pasar yang sekaligus sebagai variabel moderasi, dan variabel dependen adalah kinerja bank. Hipotesis diuji menggunakan regresi linier berganda dengan random effect model. Secara umum, hasil mendukung bahwa struktur pasar berpengaruh positif signifikan terhadap kinerja bank. Hasil lainnya menunjukkan tidak terdapat perilaku kolusif di antara bank-bank besar. Kata kunci: . Structure-Conduct-Performance, Bank Umum, BPR, Struktur Pasar, Kinerja Bank.